Improvement of Physicomechanical Properties of Pineapple Leaf Fiber Reinforced Composite - K. Z. M. Abdul Motaleb; Md Shariful Islam; Mohammad B. Hoque (International Journal of Biomaterials)
Pineapple leaf fiber (PALF) reinforced polypropylene (PP) composites were prepared by compression molding. The fiber content varied from 25% to 45% by weight. Water uptake percentages of the composites containing various wt% of fiber were measured. All the composites demonstrated lower water uptake percentages and maximum of 1.93% for 45 wt% PALF/PP composite treated with 7(w/v)% NaOH. Tensile Strength (TS), Tensile Modulus (TM), Elongation at Break (Eb %), Bending Strength (BS), Bending Modulus (BM), and Impact Strength (IS) were evaluated for various fiber content. The 45 wt% PALF/PP composite exhibited an increase of 210% TS, 412% TM, 155% BS, 265% BM, and 140% IS compared to PP matrix. Moreover, with the increasing of fiber content, all the mechanical properties increase significantly; for example, 45 wt% fiber loading exhibited the best mechanical property. Fibers were also treated with different concentration of NaOH and the effects of alkali concentrations were observed. The composite treated with 7 (w/v)% NaOH exhibited an increase of 25.35% TS, 43.45% TM, 15.78% BS, and 52% BM but 23.11% decrease of IS compared to untreated composite. Alkali treatment improved the adhesive characteristics of fiber surface by removing natural impurities, hence improving the mechanical properties. However, over 7% NaOH concentration of the tensile strength of the composite reduced slightly due to overexposure of fibers to NaOH.